Shadow captain - Reynolds, Alastair, 1966- (Reynolds, Alastair, 1966- Revenger, 2019)
"Adrana and Fura Ness have finally been reunited, but both have changed beyond recognition. Once desperate for adventure, now Adrana is haunted by her enslavement on the feared pirate Bosa Sennen's ship. And rumors of Bosa Sennen's hidden cache of treasure have ensnared her sister, Fura, into single-minded obsession. Neither is safe; because the galaxy wants Bosa Sennen dead and they don't care if she's already been killed. They'll happily take whoever is flying her ship"--